The strategic game of citizen security in Argentina (1996-2011) - Constantino, Gabriel (Cuadernos de Gobierno y Administración Pública, 2015)
The aim of this article is reconstruct the strategic game behind the formulation of citizen security policies in the main Argentine´s provinces between 1996 and 2011. The central hypothesis of this work consider that governors are the actors with capacities and interests to pursue a policy of security of left or right according to their plan of campaign, which responds to other factors which are not the alleged police interests: mainly the ideology of the national executive and the location of the median voter. The corroboration of this hypothesis instructs on the strategic game behind securities policies and the relative autonomy of the police and the penal system in Argentina.
Keywords: Citizen Security Policies; Governors; Police